2008
DOI: 10.1186/1471-2121-9-25
|View full text |Cite
|
Sign up to set email alerts
|

An intracellular motif of GLUT4 regulates fusion of GLUT4-containing vesicles

Abstract: Background: Insulin stimulates glucose uptake by adipocytes through increasing translocation of the glucose transporter GLUT4 from an intracellular compartment to the plasma membrane. Fusion of GLUT4-containing vesicles at the cell surface is thought to involve phospholipase D activity, generating the signalling lipid phosphatidic acid, although the mechanism of action is not yet clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In fact, each GLUT carrier displays a number of particular features which are the suitable and essentials for energy requirements and proper function of the specific tissue where the GLUT is expressed. For example, GLUT4 is primarily expressed in insulin-sensitive tissues, where is able to translocate from an intracellular pool to plasma membrane [ 12 – 15 ]. Each tissue displays changes in energy requirements due to their particular physiology (e.g., skeletal muscle), so the glucose uptake must be adapted for these tissue specific requirements through internal or external stimuli directly related to tissue function, such as insulin or exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, each GLUT carrier displays a number of particular features which are the suitable and essentials for energy requirements and proper function of the specific tissue where the GLUT is expressed. For example, GLUT4 is primarily expressed in insulin-sensitive tissues, where is able to translocate from an intracellular pool to plasma membrane [ 12 – 15 ]. Each tissue displays changes in energy requirements due to their particular physiology (e.g., skeletal muscle), so the glucose uptake must be adapted for these tissue specific requirements through internal or external stimuli directly related to tissue function, such as insulin or exercise.…”
Section: Discussionmentioning
confidence: 99%
“…When insulin binds to its receptor, GLUT4 is rapidly translocated to plasma membrane, increasing glucose uptake in the cell [ 6 ]. This translocation is probably mediated by a putative phosphatidic acid-binding motif, located in the cytoplasmic loop between helices 2 and 3 [ 12 ]. In addition, GLUT4 translocation can also be triggered by exercise probably through the activation of insulin-independent AMPK (AMP-activated protein kinase) pathway [ 6 ].…”
Section: Expression and Roles Of Sugar Transporters In Normal Tissmentioning
confidence: 99%
“…Glut4 is normally present on intracellular vesicles but translocates to the plasma membrane on insulin stimulation via PKB signalling (Hill et al, 1999;Wang et al, 1999) which is constitutively high in mutant 6.5. Significantly, PKB and other factors reported to be essential in Glut4 translocation, namely PKCz and Pld1 (Bandyopadhyay et al, 2001;Heyward et al, 2008) were also represented in group A. Hk2 and Gpi1 catalyze the two first steps in the glycolytic pathway. Pfk1 catalyzes the rate-limiting step that irreversibly commits glucose to the glycolytic pathway.…”
Section: Positive Gene Enrichment Analysis For Group a And B Genesmentioning
confidence: 99%
“…Mutation of these four residues individually into alanine residues within full-length GLUT4 revealed (1) that the mutation W105A increased cell surface GLUT4 levels in basal and insulinstimulated adipocytes while increasing cell surface GLUT4 recycling, (2) that K109A and R110A mutants displayed a reduction in cell surface recycling (and reduced cell surface levels) in insulin-stimulated adipocytes and (3) that the L106A mutant did not differ from wild-type GLUT4. Of note, mutation of the four residues S 103 QWL 106 en bloc into alanine residues reduced insulin-induced GLUT4 translocation by ∼20% (Heyward et al, 2008 and our own results, data not shown). Mutation of such a relatively large sequence (i.e.…”
mentioning
confidence: 97%
“…It is possible that this domain might just need to be positioned within close proximity of the membrane in order to induce intracellular retention. Maybe this is related to the potential interaction of domain II with membrane lipid phosphatidic acid (Heyward et al, 2008). Moreover, it could possibly explain why domain II induced retention of full-length CD4 (40 cytoplasmic residues) but not of full-length TfR (67 cytoplasmic residues), though this could also be due to interference from other motifs within the TfR cytoplasmic domain.…”
mentioning
confidence: 97%